THE RELEVANCE OF ACCOUNTING INFORMATION AND FINANCIAL DISTRESS OF LOCAL GOVERNMENT IN EAST JAVA - Rianto Prasetyo Wibowo; Agus Samekto (STIE Perbanas Surabaya, 2013)
Financial distress is an inability of local government to give public services appropriate with minimumstandards of service caused by lack of funds. This condition is a negative signal of local governmentbecause reflects bad governments performance. The aim of this research is examining accounting informationrelevance to financial distress of local government in East Java. Accounting informationrelevance is measured by ROA, POSGW, PERGW, CLGW, CL and DTR. Whereas, local governmentsfinancial distress is measured by DSCR based on the decree issued by the government No. 54 year 2005concerning regional loans. The sample of this research is local government in East Java both countiesand cities. Census method is used to collect the samples because every element in the population is usedas samples. Pearsons correlation product is used to analyze the data. The statistical test result showsthat POSGW, CLGW, CL and DTR have a strong enough relationship and unidirectional to DSCR.This result is in line with agency theory which states that local government will seek to minimize financialdistress condition by optimizing their financial performance. It can be concluded that accountinginformation relevance has a relationship to local governments financial distress.